Near ultraviolet transient explorer (NUTEx): a CubeSat-based NUV imaging payload for transient sky surveys - Ghatul, Shubham; Mohan, Rekhesh; Murthy, Jayant; Safonova, Margarita; Kumar, Praveen; Gopinathan, Maheswar; Jain, Shubhangi; Mahesh Babu, S. (Frontiers in Astronomy and Space Sciences, 2025)
The Near Ultraviolet Transient Explorer (NUTEx) is a CubeSat-based near-ultraviolet (NUV) imaging payload designed for transient sky surveys and is currently under development. CubeSats are compact and cost-effective satellite platforms that have emerged as versatile tools for scientific exploration and technology demonstrations in space. NUTEx is an imaging telescope operating in the 200–300 nm wavelength range, intended for deployment on a micro-satellite bus. The optical system is based on a Ritchey–Chrétien (RC) telescope configuration, featuring a 146-mm primary mirror. The detector is a photon-counting microchannel plate (MCP) device with a solar-blind photocathode, paired with an in-house-developed readout unit. The instrument has a wide field of view (FoV) of 4°, a peak effective area of approximately 18 cm2 at 260 nm, and can reach a sensitivity of 21 AB magnitude (SNR = 5) in a 1200-s exposure. The primary scientific objective of NUTEx is to monitor the night sky for transient phenomena, such as supernova remnants, flaring M-dwarf stars, and other short-timescale events. The payload is currently scheduled for launch in Q2-2026. This paper presents the NUTEx instrument design, outlines its scientific goals and capabilities, and provides an overview of the electronics and mechanical subsystems, including structural analysis.